Penerapan Knowledge Management System Sebagai Sarana Pertumbuhan Organisasi pada PT Intimap - Ce, Win; Hendra, Hendra (Bina Nusantara University, 2011)
This article discusses aout the knowledge management system implementation as growth tool at PT Intimap. The purpose of this study is to give solution to problems faced by PT Intimap, related to knowledge and the resources they own. Method used for the system development is the SDLC. Analysis shows that PT Intimap is a company with vast amount of knowledge. However, the knowledge has not been managed very carefully. Hence, there is a need to an integrated system, where all employees can put their knowledge and look for what they want to know within the system.